A Comparative Clinical Evaluation of Efficacy of Midazolam as an Adjuvant to Bupivacaine in Brachial Plexus Block by Supraclavicular Approach for Upper Limb Surgery - Dhakal, Y; Rajbhandari, R; Agarwal, T N (Journal of Nepalgunj Medical College, 2018)
Introduction: Brachial plexus block is useful as a sole regional anesthetic technique for upper limb surgeries. Adjuvants to local anesthesia may enhance quality and duration of analgesia. Our study aimed to evaluate efficacy and safety of midazolam added to brachial plexus block. Methods: 394.50 ±46.874 243 ± 57.545 Addition of midazolam to bupivacaine for brachial plexus block prolongs the duration of analgesia with lower pain scores during post-operative period. A prospective, randomized, double blind study was conducted on 60 ASA I or II adult patients undergoing upper limb surgeries under single-shot supraclavicular brachial plexus block. Patients were randomly divided into two groups. Patients in Group B (n = 30) were administered 30 mL of 0.5% bupivacaine and Group BM (n = 30) were given 30 mL of 0.5% bupivacaine with midazolam 2mg. Hemodynamic variables (i.e., heart rate, noninvasive blood pressure), pain scores, onset of motor and sensory block, duration of analgesia and sedation score and were recorded intraoperatively and postoperatively. Results: The duration of analgesia was significantly prolonged (P<0.05) in midazolam group (394.50 ±46.874 ) compared to control group (243 ±57.545). Similarly, pain scores were significantly lower in group BM than in group B (P<0.05). The onset of motor and sensory block, sedation score and hemodynamic variables were comparable between groups. No adverse events were observed during study. Conclusion: Addition of midazolam to bupivacaine for brachial plexus block prolongs the duration of analgesia with lower pain scores during post-operative period. JNGMC, Vol. 14 No. 2 December 2016, Page: 26-29